Digital Health Education Based on Huyula Gorontalo Local Wisdom for Stunting Prevention - Rachmawaty Hunawa; Dewi Suryaningsi Hiola; Nurdiana Djamaluddin (An Idea Nursing Journal, 2026)
Background: Stunting is a nutritional issue that can adversely affect physical growth, cognitive development, and long-term health outcomes. Adolescents and prospective brides represent a critical target group, as their knowledge and attitudes significantly influence maternal and child health Objective: To evaluated the effectiveness of “Huyula Gorontalo,” a digital transformation grounded in local wisdom, as an educational medium to improve knowledge and attitudes regarding stunting prevention among adolescents and prospective brides Methods: A quantitative approach was employed, utilizing a quasi-experimental design with a pre-test and post-test one-group method. Data were collected using validated questionnaires measuring knowledge and attitudes related to stunting prevention. The sample comprised 67 adolescents and prospective brides, selected through accidental sampling in the Tilango Public Health Center area, Gorontalo. The intervention consisted of digital health education based on the local cultural concept of “Huyula,” which emphasizes cooperation, collective responsibility, and community support. Results: Indicated a significant improvement in participants’ knowledge and attitudes following the intervention. The mean knowledge score increased from 2.3881 to 2.9403 (p = 0.000), and the proportion of participants with good knowledge rose from 44.8% to 94.0%. Attitudes also improved, with the mean score increasing from 1.8209 to 1.9701 (p = 0.001), and the percentage of respondents with positive attitudes rising from 82.1% to 97.0%. Conclusion: The “Huyula Gorontalo” digital transformation approach effectively enhanced knowledge and attitudes toward stunting prevention. This strategy has the potential to support sustainable health education among adolescents and prospective brides.